Pengalihan Anggaran dan Akuntabilitas Publik terhadap Infrastruktur di Desa Kecipir, Kabupaten Brebes - Muhammad Kuntoro; Titi Rahmawati; Dwi Harini; Muhammad Badrun Zaman; Amelia Sholeha (Universitas Muhadi Setiabudi, 2019)
This study aims to examine the effect of budget diversion and public accountability on infrastructure in Kecipir Village, Brebes Regency. The population of this study is the people of Kecipir Village in Brebes Regency. This research is a descriptive research with a quantitative approach that uses primary data as a source of data. Data collection techniques in the form of field research (field research). The results showed that the budget transfer variable had an effect of 36% and significantly affected the infrastructure in Kecipir Village. It is known that according to respondents, public accountability is related to the government's accountability for budget management whose source of the budget is people's funds, the public accountability variable affects 64% and significantly affects infrastructure in Kecipir Village. It is known that according to respondents, public accountability is related to the government's accountability for budget management, the source of which is people's funds.